RXFP1 is Targeted by Complement C1q Tumor Necrosis Factor-Related Factor 8 in Brain Cancer - Thanasupawat, Thatchawan; Glogowska, Aleksandra; Burg, Maxwell; Wong, G. William; Hoang-Vu, Cuong; Hombach-Klonisch, Sabine; Klonisch, Thomas (Frontiers in Endocrinology, 2015)
The relaxin-like - RXFP1 ligand-receptor system has important functions in tumor growth and tissue invasion. Recently, we have identified the secreted protein, CTRP8, a member of the C1q/ Tumor Necrosis Factor-related protein (CTRP) family, as a novel ligand of the relaxin receptor RXFP1 with functions in brain cancer. Here we review the role of CTRP members in cancers cells with particular emphasis on CTRP8 in glioblastoma.